Depth estimation from vision based wireless monocular camera sensor for soccer robot applications in MiroSot middle league - Mohd Nadhir Ab Wahab (School of Mechatronic Engineering, 2012)
This research attempts to develop a monocular vision system based control for soccer robots using depth estimation from asingle wireless camera mounted on mobile robot. This interface is planned to be employed in a MiroSot competition. The idea behind this application is to create an alternative for the current vision system used in MiroSot.